The place of technology in the Capability Approach. (2nd January 2018) - Haenssgen, Marco J.; Ariana, Proochista
Abstract: Increasing scholarly attention has focussed on how to integrate technology within the Capability Approach (CA), yet without a consistent solution. Some describe technology as a special kind of capability input, but others consider the concept of technology to be fundamentally different from that of an ordinary input. We aim to contribute to the theoretical development of the CA by offering a consistent justification for the explicit inclusion of technology in this framework. We propose that technical objects have a 'generative' and a 'transformative' dimension through which they enable capabilities directly and affect other inputs in the attainment of valued capabilities. The objects acquire the transformative dimension from the broader technological context, which we propose as a new class of conversion factors. Using the example of mobile phones and their role in healthcare access, we demonstrate that our proposal helps to frame the analysis of the development impact of technology.